2010
DOI: 10.1093/eurheartj/ehq030
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapeutic concepts * The epidemic of cardiovascular disease in the developing world: global implications

Abstract: The epidemic of cardiovascular disease (CVD) is a global phenomenon, and the magnitude of its increase in incidence and prevalence in low- and middle-income countries (LIMIC) has potentially major implications for those high-income countries that characterize much of the developed world. Cardiovascular disease remains the leading cause of death in the world and approximately 80% of all cardiovascular-related deaths occur in LIMIC and at a younger age in comparison to high-income countries. The economic impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
299
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(320 citation statements)
references
References 78 publications
5
299
0
11
Order By: Relevance
“…16,17 Furthermore, our study confirms the role of traditional CVD risk factors on PA D prevalence (Table 1), which have been consistently reported as major predictors of morbidity and mortality, 18 and support the argument for PA D prevalence variation depending on the population distribution of CVD risk factors. 1,15 Finally, our results corroborate previously reported observations of a cross-sectional study conducted in Bucaramanga, Colombia. This established the prevalence of CVD risk factors in a random sample of the general population (2989 subjects, 15---64 years old), showing that smoking, hypertension, obesity, high cholesterol, and diabetes were significantly prevalent, calling for actions to control the ongoing CVD epidemic.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…16,17 Furthermore, our study confirms the role of traditional CVD risk factors on PA D prevalence (Table 1), which have been consistently reported as major predictors of morbidity and mortality, 18 and support the argument for PA D prevalence variation depending on the population distribution of CVD risk factors. 1,15 Finally, our results corroborate previously reported observations of a cross-sectional study conducted in Bucaramanga, Colombia. This established the prevalence of CVD risk factors in a random sample of the general population (2989 subjects, 15---64 years old), showing that smoking, hypertension, obesity, high cholesterol, and diabetes were significantly prevalent, calling for actions to control the ongoing CVD epidemic.…”
Section: Discussionsupporting
confidence: 91%
“…1 These gender-based prevalence differences could be related to ''unidentified risk factors'' or might represent a survival advantage for women, with men being more likely to experience death from concomitant coronary heart disease. 15 In addition, our study shows, as well as in many others, that the ABI increased with aging. 2 ---4 This is probably due to an increased prevalence of other atherosclerosis risk factors with aging, which also triggers the progression of PAD.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A therosclerosis is a leading cause of human morbidity and mortality (Gersh et al, 2010;Go et al, 2013). Gene therapy for atherosclerosis has shown promise in several preclinical studies (Rissanen and Yla-Herttuala, 2007;Williams et al, 2010); however, other than a pilot study of low-density lipoprotein receptor gene therapy to prevent premature atherosclerosis in patients with familial hypercholesterolemia carried out nearly two decades ago (Grossman et al, 1995), gene therapy for atherosclerosis remains at the preclinical stage (Williams et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous cross‐sectional studies in both adult and pediatric populations have shown a thicker IMT in blacks and males compared with whites and females 1, 12. These studies also have shown some associations of IMT with several anthropometric variables (eg, age, sex, race, BMI), chronic stress (eg, socioeconomic status), and hemodynamic variables (eg, blood pressure and pulse pressure).…”
Section: Introductionmentioning
confidence: 93%